Simulating temperature behavior of a cracking furnace cold-wall by means of passive thermography - Heriansyah, Rudi (Penerbit UTM, 2007)
Infrared thermography (IRT) is a method to read the temperature behavior of an inspected object by using a thermal camera [1]. IRT has attracted much attention over other nondestructive evaluation techniques due to its contactless and remote nature, it is easy to interpret the thermal data from the camera, and it is free from any dangerous radiation to the thermographer. Compared to other temperature measurement devices, such as the thermocouple, a thermal camera has a wide coverage area of inspection. In IRT, numerical modeling is a precious tool, since the limits of IRT technique for a certain applications can be studied. In addition, the temperature behavior of inspected object can be investigated with various geometries and defect type without the need of making and testing the corresponding specimens [2]. Other purpose of numerical modeling in IRT is to generate a thermogram from a real world object in order to know the real thermogram property if captured by a thermal camera [3]. This thermogram can be used to test the developed algorithms (mainly related to image processing) in case of the unavailability of the thermogram from the real object, for instance due to difficulties in obtaining such thermal data.